Numerical Solution of Time Fractional Gas Dynamics Equation - R.Ramesh Rao, T.; Santosh Balaji, R. (International Journal of Engineering and Technology, 2018)
In this paper, we propose new technique for solving time fractional gas dynamics equation using Laplace-Adomian Decomposition method coupled with fractional complex transform. It is found that the tested examples reveal the present method is more reliable and does not require strong assumptions.Â Â